"Young Artists Can Try Out Everything": Redefining Contemporary Ghanaian Art in the 21st century. Issue 1 (2nd January 2019) - Woets, Rhoda
Abstract : This article discusses general changes in Ghana's contemporary art infrastructure and understandings of art in the 21st century in relation to societal processes such as liberalization, globalization and commercialization of the public arena, growing exchange with other African countries and international interest in the art scene in Ghana. I seek to demonstrate how local and international developments led to the emergence a group of artists and art institutions who stand for work that deals with social, historical, political or personal issues or emotions, who embrace new media forms and materials, such as discarded or everyday objects, and who break out of the confines of the gallery by making site-specific work. In these shifting contexts of increasing global connectivity, new and redefined artistic discourses emerged that conflicted with older, resilient art frames.